Screening of Rhizospheric Actinomycetes for Various In-vitro and In-vivo Plant Growth Promoting (PGP) Traits and for Agroactive Compounds - Anwar, Sumaira; Ali, Basharat; Sajid, Imran (Frontiers in Microbiology, 2016)
In this study 98 rhizospheric actinomycetes were isolated from different wheat and tomato fields, Punjab, Pakistan. The isolates were characterized morphologically, biochemically and genetically and were subjected to a comprehensive in vitro screening for various plant growth promoting (PGP) traits. About 30% of the isolates screened were found to be the promising plant growth promoting rhizobacteria (PGPRs), which exhibited maximum genetic similarity (up to 98-99%) with different species of the genus Streptomyces by using16S rRNA gene sequencing. The most active indole acetic acid (IAA) producer Streptomyces nobilis WA-3, Streptomyces Kunmingenesis WC-3 and Streptomyces enissocaesilis TA-3 produce 79.5, 79.23 and 69.26 µg/ml IAA respectively at 500µg/ml L-tryptophan. The highest concentration of soluble phosphate was produced by Streptomyces sp. WA-1 (72.13 mg/100ml) and S. djakartensis TB-4 (70.36 mg/100ml). All rhizobacterial isolates were positive for siderophore, ammonia and hydrogen cyanide production. Strain S. mutabilis WD-3 showed highest concentration of ACC-deaminase (1.9 mmol /l). For in-vivo screening, seed germination and plant growth experiment were conducted by inoculating wheat (Triticum aestivum) seeds with the six selected isolates. Significant increases in shoot length was observed with S. nobilis WA-3 (65 %), increased root length was recorded in case of S. nobilis WA-3 (81 %) as compared to water treated control plants. Maximum increases in plant fresh weight were recorded with S. nobilis WA-3 (84 %), increased plant dry weight was recorded in case of S. nobilis WA-3 (85 %) as compared to water treated control plants. In case of number of leaves, significant increase was recorded with S. nobilis WA-3 (27 %) and significant increase in case of number of roots were recorded in case of strain S. nobilis WA-3 (30 %) as compared to control plants. Over all the study revealed that these rhizospheric plant growth promoting (PGP) Streptomyces are good candidates to be developed as bioferlizers for growth promotion and yield enhancement in wheat crop and can be exploited for the commercial production of different agro-active compounds.